[OP.1A.06] HYPERTENSIVE TARGET ORGAN DAMAGES ARE BETTER ASSOCIATED WITH CENTRAL THAN BRACHIAL BLOOD PRESSURE: THE NORTHERN SHANGHAI STUDY. (September 2016) - CHI, C.; Yu, S.; Bai, B.; Wang, K.; Wang, L.; Lu, Y.; Zhang, Y.; Xu, Y.
Abstract : Objective: Central blood pressure (BP) is reported to associate with target organ damages (TODs) better than brachial BP. However, data regarding the association of TODs with central and brachial BP in the community-dwelling health elderly are scare. We therefore hypothesized that TODs are better associated with central than brachial blood pressure (BP) in the elderly community-based population, with considering all hypertensive TODs, namely left ventricular hypertrophy (LVH), left ventricular (LV) diastolic dysfunction (DD), carotid plaque, arteriosclerosis and microalbuminuria. Design and method: 1, 599 (44.5% men, aged 71.4 ± 6.1) participants in 4 communities in northern Shanghai were recruited. Central BP were measured with a validated device (SphygmoCor, AtCor, Australia), and brachial BP was assessed three times with mercury sphygmomanometer and the mean values were calculated. LV mass, LVDD and carotid plaque was measured by ultrasound. Arteriosclerosis was assessed by carotid-cerebral pulse wave velocity (PWV) and microalbuminuria was assessed by the ratio of urinary albumin and creatinine. Results: In univariate analyses, both central and brachial BP were significantly correlated with TODs, whereas PWV was more strongly associated with central BP as compared with brachial BP in the Fisher transformation test (P = 0.005). In the multivariate analyses, after adjustment for confounders, central BP was significantly associated with LVMI, E/Ea, LIMT and PWV in the linear regression model (P <= 0.004), whereas brachial BP was only significantly associated with E/Ea and PWV (P <= 0.005). Moreover, in the stepwised multivariate logistic regression analyses, central BP was significantly associated with LVH, LVDD, arteriosclerosis and UAC, while brachial BP failed to associate with any TODs. Similarly, when central and brachial BP were separately put in the logistic model, central BP was significantly associated with all TODs, whereas brachial BP was significantly associated with LVH and arteriosclerosis. Receiver operating characteristic (ROC) analyses indicated that central BP showed larger area under curve than brachial BP in identifying arteriosclerosis (0.755 vs 0.672, P < 0.001) and MAU (0.615 vs 0.578, P = 0.01), and similar findings were obtained in sensitivity analyses in participants without anti-hypertensive agents(n = 800). Conclusions: In a community-based elderly population, Central BP showed its superiority over brachial BP in identifying hypertensive TODs. Figure. No caption available.